KEGIATAN TARI KREASI DALAM MENINGKATKAN KEPERCAAAN DIRI ANAK USIA 5-6 TAHUN DI SANGGAR PANGSUMA M’PAGUK KABUPATEN SEKADAU - Monika Sheles; Marmawi Marmawi; Annisa Amalia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to analyze creative dance activities in increasing the confidence of children aged 5-6 years at Sanggar Pangsuma M'Paguk, Sekadau Regency. The research method used is descriptive qualitative research with phenomenological research type. Data collection tools through observation sheets, interview guidelines and documentation, with data sources 8 children. The general problem in this study is to describe how creative dance activities increase the self-confidence of children aged 5-6 years in Sanggar Pangsuma M'paguk, Sekadau Regency. The results showed self-confidence from the aspect of (1) Self-efficacy belief can be shown that children are not shy to demonstrate movements, introduce themselves in front of a loud voice, can lead prayers and warm up. (2) Optimism can be shown by children being enthusiastic in participating in creative dance activities, believing they can perform dance well. (3) The objective can be shown that the child can adjust the movement to the accompaniment of music and facial expressions according to the dance theme. (4) Being responsible can be shown that the child can work together to tidy up the tools after the activity, carrying out the trainer's direction until it is finished. (5) Rational and realistic can be shown that children can dance with flexibility, according to the count and musical accompaniment.